Genome-wide analysis of genes encoding core components of the ubiquitin system during cerebral cortex development - Alexandre Bouron; Marie-Odile Fauvarque (Molecular Brain, 2022)
Abstract Ubiquitination involves three types of enzymes (E1, E2, and E3) that sequentially attach ubiquitin (Ub) to target proteins. This posttranslational modification controls key cellular processes, such as the degradation, endocytosis, subcellular localization and activity of proteins. Ubiquitination, which can be reversed by deubiquitinating enzymes (DUBs), plays important roles during brain development. Furthermore, deregulation of the Ub system is linked to the pathogenesis of various diseases, including neurodegenerative disorders. We used a publicly available RNA-seq database to perform an extensive genome-wide gene expression analysis of the core components of the ubiquitination machinery, covering Ub genes as well as E1, E2, E3 and DUB genes. The ubiquitination network was governed by only Uba1 and Ube2m, the predominant E1 and E2 genes, respectively; their expression was positively regulated during cortical formation. The principal genes encoding HECT (homologous to the E6-AP carboxyl terminus), RBR (RING-in-between-RING), and RING (really interesting new gene) E3 Ub ligases were also highly regulated. Pja1, Dtx3 (RING ligases) and Stub1 (U-box RING) were the most highly expressed E3 Ub ligase genes and displayed distinct developmental expression patterns. Moreover, more than 80 DUB genes were expressed during corticogenesis, with two prominent genes, Uch-l1 and Usp22, showing highly upregulated expression. Several components of the Ub system overexpressed in cancers were also highly expressed in the cerebral cortex under conditions not related to tumour formation or progression. Altogether, this work provides an in-depth overview of transcriptomic changes during embryonic formation of the cerebral cortex. The data also offer new insight into the characterization of the Ub system and may contribute to a better understanding of its involvement in the pathogenesis of neurodevelopmental disorders.